Learning Islamic Religious Education Based on Spiritual and Emotional Intelligence to Build the Morals of Zainul Hasan Genggong Islamic University Students - Ainur Rofiq Sofa; H. Mundir; H. Ubaidillah (Yayasan Adra Karima Hubbi, 2024)
Background. Learning Spiritual and Emotional Intelligence in the world of education is a moral cultivation that must be owned by someone. This is because of the increasing promiscuity which is a moral decline for our teenagers today. Zainul Hasan Genggong Islamic University is a university that in addition to building intellectual intelligence also prioritizes Spiritual and Emotional Intelligence which is taken through the process of Hablum MinAllah Purification of the soul and Hablum Minannaas. Objectives. For this reason, this research was conducted, which aims to reveal Islamic religious education learning based on spiritual and emotional intelligence to foster the morals of Zainul Hasan Genggong Islamic University students. Methods. In this study, the author used a qualitative approach. By using a descriptive research model. While the methods used, namely observation, in-depth interviews, and documentation with data collection using the types of Mitode Triangulation and Source Triangulation. Results Learning Islamic Religious Education Based on spiritual and emotional intelligence to build student morals taken through Hablum MinAllah and Hablum Minannaas using the books Mahfudzot Fadoilul Iman, Mahfudzot Fadhoilun Nabi Wa Ash Shahabah, and Genggong Islamic Boarding School Philosophy proved to be able to shape the morals of Unzah students very well and religiously. Conclusion The results showed that: (a) Spiritual and Emotional Intelligence to build the morals of Unzah students was taken through Hablum MinAllah and Hablum Minannaas. (b) Islamic Religious Education learning courses based on spiritual and emotional intelligence to build the morals of Unzah students include the books Mahfudzot Fadoilul Iman, Mahfudzot Fadhoilun Nabi Wa Ash Shahabah, and Genggong Islamic Boarding School Philosophy which are basically interrelated, fill and complement the content. (c) steps for the formation of Spiritual and Emotional Intelligence to build the morals of Unzah students through Islamic Religious Education subjects in students carried out using the Tikrar Method approach, the strategy through the repetition of Quranic postulates